Methods and techniques of study as a complement to lifelong learning and professional life - Casquilho-Martins, I.; Belchior-Rocha, H.; Almeida, F.; Picornell-Lucas, A. (WCLTA 2018 9th World Conference on Learning, Teaching and Educational Leadership, 2018)
Abstract id: 29499